Usability qualities of 'well-designed' geography textbook visuals. Issue 1 (2nd January 2021) - Behnke, Yvonne
Abstract: This contribution evaluates opportunities and challenges concerning the conception and utilization of visuals in current German geography textbooks from multidisciplinary theoretical perspectives. The designer's point of view, with insights from visual communications, information design, user experience design, and instructional design, will be discussed, together with the findings from work in the fields of media studies, educational psychology, and geography education. Based on the theoretical approach, a discussion will be put forth regarding the usability aspects of visual design features in geographical learning media, relations between visual attention, visual search strategies, visual literacy skills, instructional design strategies, subject didactics, and motivational aspects of knowledge construction through today's multimodal geography textbooks. This contribution suggests six usability qualities of visual design elements in textbooks that may affect learning motivation and knowledge construction: aesthetics (visual appealing), (quick and easy) orientation, usefulness (relevant information complementing text information), helpfulness (support with completing tasks and content comprehension), interest (relevant content, new perspectives), and comprehensibility (image content connects to the topic). A model embeds the evolved usability qualities of 'well-designed' textbooks into existing theoretical models from the fields of educational psychology, visual communications, media studies, and geography education.